Cross-border mobility of Poles at the beginning of the 21st Century - WIECKOWSKI, Marek (Discussion Papers, 2011)
The liberalisation of the boundary regime, along with the course of the socio-economic processes (improvement of life quality, broadening of individual capacities, more free time), entailed the increase of cross-boundary mobility beyond Polish borders. The reasons for travel are diverse, frequently multi-motivational. Tourism as a higher-level good is still in the initial phase (strictly-defined tourist traffic accounts for a couple to a dozen or so per cent of the entire cross-border mobility). It is very difficult to demonstrate which of the elements of development of cross-border mobility has a decisive significance. There exist, namely, numerous external and internal elements which influence to different degrees the development and functioning of this kind of mobility. These elements include, in particular: the degree of openness of boundaries, relations of prices and currency exchange rates, tourist offers (both tourist attractions and quality of service), fashion trends, preferences, skills in introduction of innovations, and quality of human capital. The mobility of Poles in terms of international departures, which were unimaginable and impossible a generation earlier, is still a combination of tourism trips, labour migration and trade, the large majority of this traffic consisting of one-day visitors in the neighbouring countries. In analyzing Polish international mobility it is possible to note several essential changes: an increase of international mobility, an increasing complexity of the migration and tourism movement and a change of motives for departures. Generally known reasons of the increasing of Poles’ mobility are the opening of the borders and abolition process in visa obtain and the improvement of communication, especially growth of the number of links with other European countries. The economic transition following Poland’s entry into the EU in the 2004 had mainly positive consequences for Poles.